Effect of Implant Diameter on its Survival Rate among a Group of Iranian Warfare Victims Presenting to QaziTabatabai Clinic Affiliated to Shahid Beheshti University during 2000-2010 - Jafarian, Mohammad; Bayat, Mohammad; Emadi, Naghmeh; Pakravan, Amir-Hossein (Journal of Dental School, 2020)
Objective: At present, treatment of edentulous areas with implant-supported prosthesis has greatly increased. The aim of this study was to assess the survival rate of implants with different diameters. Methods: This retrospective study was conducted on 239 warfare victims presenting to Qazi Tabatabaie Clinic during 2000-2010. A total of 1,649 implants were placed. The success criteria included presence of osteointegrated implants with no sign of infection, mobility, or lucency around them. Data were extracted from patients’ records and recorded in questionnaires. Statistical analysis was carried out using Chi-square or Log-Rank test. Results: A total of 1,533 implants were evaluated out of which, 61 (4%) had failed. Survival rate of implants of different brands had a significant association with implant diameter as the highest failure rate was observed in implants with 5-6.5 mm diameter and the lowest failure rate belonged to 3-3.5 mm diameter implants. Conclusion: Study results demonstrated that the survival of implants may be affected by their diameter as the failure rate was higher in implants with greater diameters.